Peran Penyunting pada Program Komedi Seperti Kopi (KSK) di Magna Channel - Lesmono, Budi; Agustina, Dwi Pela (Jurnal Ilmiah Multimedia dan Komunikasi, 2023)
The main problem in this study is the role of editor in program Komedi Seperti Kopi (KSK) that is being broadcast in Magna Channel; both the roles as a video editor and a technical concocter in editing the KSK program. The type of research used here is field research to obtain the necessary problem data. Data collection techniques used participant observation and documentation. The data presented is in the form of screenshots of the editing works resultss or other forms of documentation during the editing process which are then presented descriptively.The results of the study show that the role and function of the KSK program editor is as an analyst to ensure image quality is in accordance with Standard Operating Procedures (SOP) and does not violate broadcasting guidelines. In carrying out these roles and functions, the editor performs censorship by cutting the image and sound (cutting), recombining (trimming) and submitting it to the quality controller when all the editing processes have been completed. Apart from that, technically, the editor does rearrangement, sound arrangement (mixing), assigns titles, and creates fillers. The editor also uses the cut technique for cutting videos, then dissolves fadein and fadeout to soften video cuts.